Simulation for Neutron Transport in PWR Reactor Moderator and Evaluation for Proper Thickness of Light Water Reflector - Khai, Nguyen Tuan; Vuong, Phan Quoc (Communications in Physics, 2015)
Monte Carlo calculation method can be used for resolving particle transport in matter, and particularly the transport of neutrons in environment of reactor core. The method has become more efficiently because of high accuracy of updated nuclear data and fast development of advanced super-computing system. In this work, we would like to present calculations for kinematical characteristics of neutron transport in a typical configuration of the pressurized water reactor (PWR) fuel assembly based on the Monte-Carlo simulation method. We concentrate in two main results: (1) neutron energy spectrum at fuel rod and (2) optimal thickness of light water reflector